Posted by **jasmine20** on Monday, April 2, 2007 at 5:49pm.

My qustion is for the following

the problem reads as follows

(x-1)^2 = 7

x-1=+- sqrt 7

x= 1+- sqrt 7

the method they use was factoring in order to simplify the equation to make it easier is this correc?

x^2-9x-4=6

x^2-9x-10=0

(x-10)(x+1)=0

What method did they use here I think its simplifying but i am not sure?

4x^2-8x+3=5

4x^2-8x-2=0

2(2x^2-4x-1)=0

2x^2-4x-1=0

here the method that they use was first factoring then simplefiying and then they will use the quadratic formula is this correct?

You are right on all counts.

## Answer this Question

## Related Questions

- algebra,math,help - Use Property 2 to simplify each of the following radical ...
- math - how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please ...
- Calculus - Please look at my work below: Solve the initial-value problem. y'' + ...
- math,algebra,help - Directions are simplify by combining like terms. x radiacal ...
- algebra - simplify: square root of 5 + square root of 20 - square root of 27 + ...
- Calculus - Second Order Differential Equations - Posted by COFFEE on Monday, ...
- Algebra 2 - Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x...
- Math - How do you find a square root of a number that's not a perfect square? I'...
- Algebra 2: Radicals URGENT!! - Could some kind, saintly soul help me solve this ...
- Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...